Doing Space while Doing Gender Vernetzungen von Raum und Geschlecht in Forschung und Politik - Habermas, Rebekka (Dynamiken von Raum und Geslecht, 2018)
This volume, which can also be used as a manual due to the linking of its contents, shows how dynamics of space and gender also affect contemporary political issues.